Introduction and 2024–2025 Update - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Cultural identity; Economic Justice; Identity (music); Inclusion (mineral); Relevance (law); Work (physics); dept.dei

Moving Forward - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Cultural center; Cultural diversity; Cultural identity; Identity (music); Multiculturalism; Politics; dept.dei

Preface - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: dept.dei

Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education - Felix, Alex Romero; Mendoza, Gary Santos; Torres-Baez, Daisy (Emerald Group Publishing Ltd., 2025)
Heart Work: The Handbook on the Survival and Success of Cultural and Identity Centers in Higher Education highlights the experiences of higher education professionals working in these centers. This handbook offers a blend of personal stories and the latest research on cultural and identity centers, building on Dr. Lori Patton Davis’ 2010 book, Culture Centers in Higher Education: Perspectives on Identity, Theory, and Practice. Since 2010, these centers have navigated significant challenges, including the global COVID-19 pandemic, and have increased focus on institutional racism. The book delves into the experiences and histories of various cultural and identity centers, including Latinx/e Cultural Centers, Asian, Pacific Islander, Middle Eastern Arab and Desi Cultural Centers, Native American/Indigenous Cultural Centers, Black/African American Cultural Centers, Disability Cultural Centers, Lesbian, Gay, Bisexual, Transgender, Queer+ Centers, and Undocumented Student Resource Centers. In light of recent events affecting minoritized populations, it also covers topics such as evolving practices in cultural/identity centers, university politics, and strategies for practitioners to advance and sustain the Heart Work. Heart Work offers community members - especially potential and current practitioners, faculty, and staff in higher education - an understanding of the recent environmental context of cultural and identity centers. As our society evolves, recognizing that identities are not monolithic and embracing intersectionality allows for a deeper understanding of oppression and lived experiences. This handbook aims to bridge the gap by continuing the research and practice of cultural and identity centers in higher education. © 2026 by Emerald Publishing Limited. All rights reserved.
Keywords: dept.dei

Celebrating and Supporting Latinidad on College Campuses: Latinx/E Cultural Centers - Felix, Alex Romero; Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Center (category theory); Cultural center; Higher education; Politics; Population; dept.dei

Supporting Native American/Indigenous Students’ Survivance Through Native American/Indigenous Cultural Centers - Torres-Baez, Daisy (Heart Work: The Handbook on the Surviving and Thriving of Cultural and Identity Centers in Higher Education, 2025)
Keywords: Cultural diversity; Ethnic group; Indigenous; Native american; Traditional knowledge; White (mutation); dept.dei

Scholars in health equity: a program of structured physician faculty development - Ring, Jeffrey; Torres, Daisy; Ramos, Rosio; Gonzalez, Cristina M.; Nahid, Musarrat; Morales, Susana; Phillips, Erica (Journal of General Internal Medicine, 2024)
Structured faculty development programs focused on integrating health equity into medical education curricula remain limited.
Keywords: adult learning theory; anti-racist curricula; dept.dei; faculty development; health equity; medical education; peer-reviewed

Educational redlining: Bridging historical contexts to contemporary practice - Rutledge, K.E; Robinson-Morris, D.W. (Resisting Divide-and-Conquer Strategies in Education: Pathways and Possibilities, 2024)
Resisting Divide-and-Conquer Strategies in Education: Pathways and Possibilities examines the ways in which divide-and-conquer strategies operate in the American public education system. In U.S. education, these mechanisms are endemic and enduring, if not always evident. Coordinated, strategic, well-funded, politically-viable campaigns continue to stoke fear, othering, villainization, and dehumanization of minoritized groups, pushing false and problematic narratives that inhibit progress toward social justice. Weaponizing hegemony and leveraging misinformation, reactionary agents and institutions seek to suppress truth, block access to democratic participation, and dismantle education and other sites of emancipatory possibility through the strength of divide-and-conquer mechanisms, pitting relatively disempowered groups against one another to preserve the dominant social order. Readers of this book will encounter conceptual and critical interrogations of divide and conquer. The text will help facilitate inquiry and engagement into how divide and conquer operates and how it can be resisted. It looks at the history of the phenomenon, as well as its current state, especially as it relates to education. What insights and lessons might we learn from a focused examination of divide and conquer, and what strategies of resistance are both possible and necessary for challenging it? This text is designed for undergraduate and graduate classrooms in education and social sciences. Part I, Ideology and Sociopolitical Contexts, dissects how divide-and-conquer mechanisms operate ideologically and sociopolitically. Part II, Policies and Practices, focuses on how divide-and-conquer mechanisms shape exclusionary U.S. educational policies and practices. Part III, Resistance and Liberation, documents efforts of liberatory communicative, curricular, and pedagogical possibilities. Each chapter concludes with a set of critical questions for reflection and engagement.Perfect for courses such as: Foundations of Education; Schools and Society; Schooling in America; History of Education; Philosophy of Education; Sociology of Education; Social Studies; Critical Theory in Education
Keywords: dept.dei

A chief diversity officer's perspective: Advocacy and allyship-how can I help? - Ariza, D. (How to Incorporate Equity and Justice in Your Teaching, 2024)
Keywords: dept.dei